«De todo ese dolor que lo precede». La poesía del exilio de Martha L. Canfield - Spadola, Carmelo (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
In this contribution we present some poems concerning the theme of exile-insile in Martha Canfield, Uruguayan-Italian poet, interpret of the political and social situation of Uruguay during the military dictatorship (1973-1985). The elected poems are contained in the first collection, Anunciaciones (1973), beyond an emblematic text titled El pasado ajeno, in which the poet reaches a very high level of dramatism.